An extended CCR5 ECL2 peptide forms a helix that binds HIV‐1 gp120 through non‐specific hydrophobic interactions. (18th March 2015) - Abayev, Meital; Moseri, Adi; Tchaicheeyan, Oren; Kessler, Naama; Arshava, Boris; Naider, Fred; Scherf, Tali; Anglister, Jacob
<x xml:space="preserve">Abstract</x> C‐C chemokine receptor 5 (CCR5) serves as a co‐receptor for HIV‐1. The CCR5 N‐terminal segment, the second extracellular loop (ECL2) and the transmembrane helices have been implicated in binding the envelope glycoprotein gp120. Peptides corresponding to the sequence of the putative ECL2 as well as peptides containing extracellular loops 1 and 3 (ECL1 and ECL3) were found to inhibit HIV‐1 infection. The aromatic residues in the C‐terminal half of an ECL2 peptide were shown to interact with gp120. In the present study, we found that, in aqueous buffer, the segment Q188–Q194 in an elongated ECL2 peptide (R168–K197) forms an amphiphilic helix, which corresponds to the beginning of the fifth transmembrane helix in the crystal structure of CCR5. Two‐dimensional saturation transfer difference NMR spectroscopy and dynamic filtering studies revealed involvement of Y187, F189, W190 and F193 of the helical segment in the interaction with gp120. The crystal structure of CCR5 shows that the aromatic side chains of F189, W190 and F193 point away from the binding pocket and interact with the membrane or with an adjacent CCR5 molecule, and therefore could not interact with gp120 in the intact CCR5 receptor. We conclude that these three aromatic residues of ECL2 peptides interact with gp120 through hydrophobic interactions that are not representative of the interactions of the intact CCR5 receptor. The HIV‐1 inhibition by ECL2 peptides, as well as by ECL1 and ECL3 peptides and peptides corresponding to ECL2 of CXCR4, which serves as an alternative HIV‐1 co‐receptor, suggests that there is a hydrophobic surface in the envelope spike that could be a target for HIV‐1 entry inhibitors. Database The structures and NMR data of ECL2S (Q186–T195) were deposited under Protein Data Bank ID 2mzx and BioMagResBank ID 25505.